Level of Science Literacy Among Drugs Abuser in Bima City and Bima Regency - Syarifatul Mubarak (Postgraduate, University of Mataram, 2023)
One of the areas in West Nusa Tenggara Province where cases of drug abuse are rampant is Bima City & Bima Regency. Data on drug abuse by the age of 15-25 years in Bima City and Bima Regency even reached 63% compare to its total case. So that researchers are interested in choosing a theme related to the level of scientific literacy of drug abusers in the Bima City & Bima Regency. This study is a quantitative study to determine the level of scientific literacy of drug abusers in Bima City and Bima Regency with a sample of 25 people and using scientific literacy instruments to collect related data. The results of the study then showed that the scientific literacy level had an average achievement of 18.93 which was in the low category. Where for the existing scientific literacy aspect, both the knowledge aspect (K) is in the low category with an average achievement percentage of 21.6% while the competency aspect (C) is in the low category with an average of 24.39%.